Electrochemical properties of modified titania nanotubes incorporated with Mn₂O₃ and Co₃O₄ for supercapacitor application - Samsudin, Nurul Asma (2017)
Highly ordered titania nanotubes (TNTs) was used in this study as it known to have a remarkable chemical stability and its open ended nanotubes structure offers large surface area and good interfacial connectivity with the electrolyte which will enhance the capacitive performance. The TNTs were synthesised by electrochemical anodisation method in two-electrode cell containing NH4F solution. Parameters affecting the morphological and geometrical aspects as well as electrochemical performance of TNTs were investigated by varying the electrolyte composition, applied anodisation voltage and anodisation time. The formation of TNTs were confirmed by x-ray diffraction (XRD) and field emission scanning electron microscopy (FESEM) analyses. Meanwhile the electrochemical performance of the TNTs were evaluated in 1.0 M KCl electrolyte using cyclic voltammetry (CV) and galvanostatic charge-discharge test in a three electrode electrochemical cell system consisted of Pt as counter electrode, Ag/AgCl (3 M KCl) electrode as reference electrode and TNTs as the working electrode. Single phase anatase TNTs were obtained upon calcination at 500 oC for samples prepared at all electrolyte compositions. FESEM revealed the nanotubes formed were uniform with well defined circular tubes. However, the tubes becomes disordered and clustered with irregular shape as the water content increased. All prepared TNTs displayed reversible unsymmetrical CV shapes with distorted anodic region and this was associated to the non-faradic charge-discharge of the oxide surface. TNTs 5 % exhibits highest current which leads to higher capacitance compared to other synthesised samples. TNTs 5% was further modified by electrochemical reduction to enhance the capacitive properties. The applied voltage and reduction time were varied to obtain the optimum condition. Excellent electrochemical performance of modified TNTs 5 % denoted as R-TNTs was observed with CV curve indicated 18 times higher in specific capacitancevalue than unmodified TNTs. Ideal capacitor behaviour and good electrochemical stability were observed for sample synthesised at applied voltage of 5 V for 30 s. A high average specific capacitance of 11.12 mF cm-2was also observed from galvanostatic charge-discharge analysis. The enhancement of the capacitive performance can be attributed to the enhancement in conductivity and electrical performance of the sample due to the introduction of oxygen vacancy by conversion of Ti4+ to Ti3+ as revealed by X-ray photoelectron spectroscopy (XPS). Pulse reverse electrodeposition was applied to deposit Mn2O3 and Co3O4 nanoparticles into the R-TNTs to further improve the capacitive performance of the samples. Electrodeposition parameter such as deposition potential, duty cycle, deposition time, concentration of metal precursor, pH of the metal precursor solution and heating temperature were varied to obtain the optimum samples XRD analysis confirmed that Mn2O3 and Co3O4 nanoparticles were successfully loaded into the R-TNTs while FESEM and TEM images revealed the presence of the nanoparticles along the R-TNTs tubes wall. Specific capacitance, as high as 37.00 mF cm-2 obtained for Mn2O3/R-TNTs and 16.89 mF cm-2 for Co3O4/R-TNTs due to the contribution of double-layered capacitance by the R-TNTs and pseudocapacitance of the metal oxides. The synthesised samples displayed a good electrochemical stability as they exhibits more than 85% capacitive retention after 1000 charge-discharge cycles.